How do you multiply 3x^2y^2z(7x^2+2y+z+4w)3x2y2z(7x2+2y+z+4w)?

1 Answer
Apr 27, 2017

21x^4y^2z+6x^2y^3z+3x^2y^2z^2+12x^2y^2zw21x4y2z+6x2y3z+3x2y2z2+12x2y2zw

Explanation:

Multiply each part of 7x^2+2y+z+4w7x2+2y+z+4w by 3x^2y^2z3x2y2z
3x^2y^2z(7x^2)=21x^4y^2z3x2y2z(7x2)=21x4y2z
3x^2y^2z(2y)=6x^2y^3z3x2y2z(2y)=6x2y3z
3x^2y^2z(z)=3x^2y^2z^23x2y2z(z)=3x2y2z2
3x^2y^2z(4w)=12x^2y^2zw3x2y2z(4w)=12x2y2zw

Then you add each part to get
21x^4y^2z+6x^2y^3z+3x^2y^2z^2+12x^2y^2zw21x4y2z+6x2y3z+3x2y2z2+12x2y2zw